2022
DOI: 10.1111/fog.12619
|View full text |Cite
|
Sign up to set email alerts
|

Modern technologies and integrated observing systems are “instrumental” to fisheries oceanography: A brief history of ocean data collection

Franklin B. Schwing

Abstract: Interdisciplinary data fuel fisheries oceanography research and the ecosystem‐based approaches to management and sustainable development it informs. Underlying this is a distributed ocean observing framework that is integrated, interoperable, interactive, and accessible. In recognition of the 30th anniversary of Fisheries Oceanography the journal, this paper reviews the evolution of observing instruments and platforms used in contemporary fisheries oceanography the science. Illustrated with personal anecdotes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 219 publications
2
5
0
Order By: Relevance
“…However, the coefficient for this relationship appears inconsistent across DOLS specifications, increasing fisheries industry sustainability by 0.03% to 0.04% for each increase in percentage in IP rights for the estimators FEOLS and FMOLS, accordingly. This research is consistent with earlier findings by Ziegler et al (2022), Scarnecchia and Schooley (2022), and Schwing (2023). Understanding the marine environment, developing the future blue economy, and realizing Europe's goal of being the first climate‐neutral continent by 2050 depends on fisheries and marine intellectual property rights.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…However, the coefficient for this relationship appears inconsistent across DOLS specifications, increasing fisheries industry sustainability by 0.03% to 0.04% for each increase in percentage in IP rights for the estimators FEOLS and FMOLS, accordingly. This research is consistent with earlier findings by Ziegler et al (2022), Scarnecchia and Schooley (2022), and Schwing (2023). Understanding the marine environment, developing the future blue economy, and realizing Europe's goal of being the first climate‐neutral continent by 2050 depends on fisheries and marine intellectual property rights.…”
Section: Resultssupporting
confidence: 93%
“…While increasing quantiles, the magnitude of the influence of intellectual property rights grows. As a result, it is showing consistency with the findings of Schwing (2023), Scarnecchia and Schooley (2022), and Ziegler et al (2022), who concluded that the protection of intellectual property rights encourages the fisheries sector to pursue more sustainable growth. In addition, a strong and positive correlation exists between market size outcomes and fisheries productivity in the medium and above‐medium quantiles.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Oceanographic monitoring systems, these systems include buoys, floats, and gliders equipped with sensors that measure parameters such as temperature, salinity, pH, and nutrient levels in the ocean. These real-time data sources provide critical information for understanding climate change, ocean acidification, and the health of marine ecosystems (Schwing, 2023). Data management and modeling, advanced data management and modeling techniques are essential for analyzing and interpreting vast amounts of marine data.…”
Section: Types Of Technology Used In Marine Policymentioning
confidence: 99%
“…All of these approaches have readily applied the use of a conceptual model for describing how ecosystem components interact and how they are scaled relative to biophysical drivers. The importance of the Stommel Diagram approach, which examines scales of spatiotemporal variability of biological and physical oceanography, is now a ubiquitous feature of biological, fisheries and ecosystem oceanography (Stommel, 1963;Haury et al, 1978;Levin, 1992;Schwing, 2023). This cornerstone approach to conceptualizing oceanographic variability extends to development of research programs invested in understanding the causal and ultimate drivers of marine ecosystem dynamics worldwide by pairing empirical and numerical modeling research priorities (e.g., Wells et al, 2020).…”
Section: A Role For Ecosystem Oceanographymentioning
confidence: 99%